A hexanucleotide repeat modifies expressivity of X‐linked dystonia parkinsonism. Issue 6 (3rd May 2019) - Westenberger, Ana; Reyes, Charles Jourdan; Saranza, Gerard; Dobricic, Valerija; Hanssen, Henrike; Domingo, Aloysius; Laabs, Björn‐Hergen; Schaake, Susen; Pozojevic, Jelena; Rakovic, Aleksandar; Grütz, Karen; Begemann, Kimberly; et al.
Abstract : Objective: X‐linked dystonia parkinsonism (XDP) is a neurodegenerative movement disorder caused by a single mutation: SINE‐VNTR‐Alu (SVA) retrotransposon insertion in TAF1 . Recently, a (CCCTCT)n repeat within the SVA insertion has been reported as an age‐at‐onset (AAO) modifier in XDP. Here we investigate the role of this hexanucleotide repeat in modifying expressivity of XDP. Methods: We genotyped the hexanucleotide repeat in 355 XDP patients and correlated the repeat number (RN) with AAO (n = 295), initial clinical manifestation (n = 294), site of dystonia onset (n = 238), disease severity (n = 28), and cognitive function (n = 15). Furthermore, we investigated i) repeat instability by segregation analysis and Southern blotting using postmortem brain samples from two affected individuals and ii) relative TAF1 expression in blood RNA from 31 XDP patients. Results: RN showed significant inverse correlations with AAO and with TAF1 expression and a positive correlation with disease severity and cognitive dysfunction. Importantly, AAO (and not RN) was directly associated with whether dystonia or parkinsonism will manifest at onset. RN was lower in patients affected by mouth/tongue dystonia compared with blepharospasm. RN was unstable across germline transmissions with an overall tendency to increase in length and exhibited somatic mosaicism in brain. Interpretation: The hexanucleotide repeat within the SVA insertion acts as a genetic modifier of disease expressivity in XDP. RN‐dependent TAF1 repression and subsequent differences in TAF1 mRNA levels in patients may be potentiated in the brain through somatic variability leading to the neurological phenotype. ANN NEUROL 2019;85:812–822.